2018
DOI: 10.1007/s10811-018-1594-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the chemodiversity of tropical microalgae for the discovery of natural antifouling compounds

Abstract: Marine microalgae and cyanobacteria have largely been studied for their biotechnological potential and proved their ability to produce a wide array of bioactive molecules. We investigated the antifouling potential of unexplored benthic tropical microalgae using anti-adhesion and toxicity bioassays against two major micro-and ma crobiofoulers, namely bacteria and barnacles. Fifty strains belonging to six phyla [Cyanobacteria, Miozoa (Dinoflagellata), Bacillariophyta, Cryptophyta, Rhodophyta and Haptophyta] were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…[3] in freshwater environments, produce toxins that can cause potential health issues. These previous findings thus encourage the implementation of an ad hoc surveillance of the toxicity of these three bloom-forming species in Moorea Island and more globally in French Polynesia, using, for instance, a non-targeted metabolomic approach [68,69] and/or other cytotoxicity-based functional assays [70].…”
Section: Discussionmentioning
confidence: 75%
“…[3] in freshwater environments, produce toxins that can cause potential health issues. These previous findings thus encourage the implementation of an ad hoc surveillance of the toxicity of these three bloom-forming species in Moorea Island and more globally in French Polynesia, using, for instance, a non-targeted metabolomic approach [68,69] and/or other cytotoxicity-based functional assays [70].…”
Section: Discussionmentioning
confidence: 75%
“…Among these technologies, the coupling of liquid chromatography to mass spectrometry (LC-MS) has gradually become an important tool to quantitative analysis of central carbon metabolites since its high throughput, good metabolites coverage and soft ionization ( Zhou et al, 2012 ). The LC-MS has been recently applied to many marine microorganisms, including explaining chemodiversity of a rich marine microorganism tropical ecosystem ( Reveillon et al, 2019 ), identifying hub metabolites relevant to resist Fe 2+ and high light stress condition in Haematococcus pluvialis ( Su et al, 2014 ), and exploring possible mechanisms of elevating fatty acid contents after overexpressing EL O3 gene in Schizochytrium sp . 31 ( Wang et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four fractions were obtained and only the methanolic fraction was studied. Previous study has shown that methanolic fractions were the most active among the screening carried out [ 63 ]. The extraction yield was defined as the amount of methanolic fraction divided by the amount of dried algal biomass.…”
Section: Methodsmentioning
confidence: 99%